Legal Review of Parking Levy at Pasar Raya Salatiga City - Muhammad Irkham Ashari; Arief Budiono (Universitas Muhammadiyah Surakarta, 2023)
Parking is something that is often encountered by the community, especially in economic activities in markets, malls and so on. Many of us also know that there are illegal parking lots that are not under the auspices of the government. This is not justified because actually parking is a retribution income in each area. This study using the Juridical Empirical method, the data source comes from primary and secondary data. In qualitative research, data analysis techniques used are data reduction, data presentation, and data verification. Checking the validity of the data using source triangulation and technical triangulation. In this research, it is known that there are still many parking attendants in Pasar Raya who do not fully know what obligations they have to do. Apart from that, there are also parking attendants who do not wear SKRD such as tickets, vests and identification. Obstacles in the implementation of the parking levy itself are still the illegal parking attendants in Pasar Raya, who come from residents of the Raya Pasar scope.